Peran Kepala Sekolah Dalam Menigkatkan Kinerja Guru Pada SMPN 9 Kendari - Chairiel, Muchammad; Mustafa, La Ode; Elwan, La Ode Muhammad (Universitas Halu Oleo, 2020)
Â The purpose of this research is to identify and describe the role of the principal in improving the performance of the study teachers at SMPN 9 Kendari . The research methodology used in this study is a descriptive method that seeks to describe the intended phenomenon. The data obtained from interviews with informants, namely 4 people who know about the role of the principal in improving teacher performance. Then the data obtained is then analyzed and interpreted and a conclusion is drawn. The results of this study are based on the results of the analysis and discussion that has been voiced, that the role of the principal in improving the performance of study teachers at SMPN 9 Kendari consists of 2 indicators, namely the role of the principal consisting of educator (educator), manager (manager), administrator, supervisor (supervisor), leader (leader), and innovator (innovator). Then the employee teacher performance consists of ability (ability) and motivation (motivation).